PREVALENCE OF HBSAG IN PATIENTS ATTENDING TERTIARY CARE HOSPITAL IN NORTHERN INDIA - SANGRAM SINGH PATE; ANUSHA VENKATESAN; CHANDRIM SENGUPTA; SURBHI KANSAL; BHAWNA (International Journal of Pharma and Bio Sciences, 2015)
The term viral hepatitis refers to a primary infection of the liver by any one of a heterogeneous group of hepatitis virus. Type B hepatitis is the most widespread and the most important type of viral hepatitis. Hepatitis B Virus infection is transmitted by parenteral, sexual or perinatal mode. Hepatitis B surface Antigen (HBsAg) detection by card test and ELISA are the most frequent techniques used for screeningThe aim of the study was to detect the prevalence of HBsAg among the patients attending tertiary care hospital in Barabanki, Uttar Pradesh, India. Blood samples that were routinely sent for HBsAg detection were included in the study. After separating the serum, card test for HBsAg and ELISA for hepatitis B antigen was performed. The numbers of samples positive for HBsAg were 128 out of 2464 total samples collected. The prevalence was highest among women. The age group having the highest prevalence rate was from 31-60 years.